A qualitative exploration of GPs' perspectives on managing chronic nonspecific musculoskeletal pain in Australian general practice – a focus group study. Issue 1 (1st February 2018) - Gaikwad, Manasi; Vanlint, Simon; Aylward, Paul; Stocks, Nigel
Abstract : Objective: Chronic nonspecific musculoskeletal pain (CNMP) is a complex idiopathic condition that causes significant disruption to patients' lives, their relationships, and functionality. The cause of CNMP is not fully understood, which makes diagnosis and management challenging. As general practitioners (GPs) are central to the management of chronic pain, their perspectives on managing CNMP are important. Purpose: To explore the clinical reasoning GPs use when diagnosing and managing CNMP. Methods: A qualitative study design using focus group discussion was conducted with Australian GPs. Five focus group discussion were conducted across Adelaide. All focus group discussions were audio-recorded, and transcripts were coded and analyzed thematically with the program NVivo. Results: The main themes remained consistent across the five focus group discussion's: the ambiguous cause of CNMP; sex differences; developing the "right strategy"; patient-centered care; and verifying vitamin D levels. Conclusion: The findings show that GPs use a patient-centered approach tailored to individual patients' medical history, physical examination findings, and psychosocial health. There was general concern about low levels of vitamin D in patients with CNMP, and vitamin D supplements were recommended if indicated by a patient's history.